ANALISIS KEPUASAN RESPONDEN TERHADAP PELAYANAN E-KTP KECAMATAN KOTO GASIB PADA TAHUN 2022 - Nadia Sofianis; Zulfa Harirah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
One form of public service that will be carried out by the government is the need for optimal community e-KTPs. However, there was a decrease in the value of the Koto Gasib community satisfaction survey and the number of printed e-KTPs, so that it became a problem that occurred at the Koto Gasib District Office, Siak Regency. The community complains about the performance of employees, causing a sense of community dissatisfaction. The eKTP service process cannot provide certainty or information related to the institution or the community. Therefore, employee performance needs to be improved again. The purpose of this study is: To measure community satisfaction with the performance of the sub-district apparatus in Koto Gasib. This research can be classified in the type of quantitative research with descriptive analysis. From the results of research that has been carried out, it is known that the percentage of respondents to community satisfaction in the quality of public services is 45.92%, which in the criteria for respondents' answers 25% -49% are categorized as dissatisfied. Keywords: Public Service, Apparatus Performance , Satisfaction Percentage